Osteoarthritis: The Challenge of Establishing a Personalised Treatment - Johanne Martel-Pelletier; Antonello Pietrangelo; Francis Berenbaum; Jean-Pierre Pelletier; Burkhard Leeb (European Medical Journal Rheumatology, 2014)
The symposium, co-chaired by Prof Johanne Martel-Pelletier and Prof Antonello Pietrangelo, opened with a discussion of metabolic syndrome-associated osteoarthritis (OA) and a brief overview of treatment options by Prof Francis Berenbaum. Prof Jean-Pierre Pelletier then discussed the use of symptomatic slow-acting drugs for OA (SYSADOA) for knee OA within the context of the new European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO) recommendations. Finally, Dr Burkhard Leeb concluded the session by discussing the indications, contraindications, and side-effect management of diacerein.